Studies on SnCl2-doped TiO2 photocatalyst for pyrocatechol photodegradation - Pierre Lecante (2018)
SnCl 2 -doped TiO 2 photocatalyst for pyrocatechol photodegradation aimed to examine the effect of Sn/Ti ratio and H 2 O 2 +UVC irradiation. The preparation was carried out by the impregnation and the characterization consisted of WAXD, SEM, and laser particle size. Using 1 mM pyrocatechol in the CSTR with various TiO 2 photocatalysts, the remaining pyrocatechol was determined by UV-vis spectrophotometry to calculate % photodegradation. From WAXD results, it was found that SnO 2 incorporation to the TiO 2 bulk phase but the morphologies did not change. And the particle size changed due to the attraction force of the surface charging. Without H 2 O 2 addition, it showed 15.7% photodegradation by TiSn10UVC compared to 11.37% of TiDark. Thus, UVC was the important factor for photodegradation. With H 2 O 2 +UVC irradiation, the maximum photodegradation reached 34.6% by TiSn10HOUVC, but those of HOUVC and TiHOUVC showed 25.0% and 26.5%, respectively. The Sn-doping affected the formation of more hydroxyl free radical from H 2 O 2 +UVC irradiation and charge separation. But higher Sn/Ti ration, it gave segregate SnO 2 which increased recombination center with the adverse effect on the lower photodegradation. The conclusion revealed that SnCl 2 -doping with the ratio of Sn/Ti =10 onto TiO 2 photocatalyst showed the highest photoactivity with H 2 O 2 +UVC irradiation. Moreover, the chemical kinetics is also discussed.